2016
DOI: 10.18535/ijsshi/v3i2.06
|View full text |Cite
|
Sign up to set email alerts
|

Education As A Key To Economic Growth And Development In Nigeria

Abstract: The aim of this paper is to analyze the impact of education on economic growth of Nigeria using ordinary test squares (OLS) to determine the relationship between education as human capital and Real Gross Domestic Product (GDP). The study therefore found that there is statistically significant relationship between GDP and all the variables used in the study with the exception of primary school enrolment (PRYE). The negative coefficient of the PRYE is also an indicator that there are problems at this level of ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
(6 reference statements)
1
8
0
Order By: Relevance
“…However RETE and RCETE are significant at 10% level of significance while PRI is significant at 5% level of significance. This outcome is in line with the results of Idrees and Saddiqi (2013) and Mallick, Das and Pradhan[1] but against the findings of Jelilov, Alenshinloye and Onder[7].The adjustment term (ECM) 1.06 implies that reversion to long run equilibrium is at an adjustment speed of about 106 percent. Finally, the granger causality test reveals that a unidirectional causality exist between SEDU and RETE, PRI and RETE, PRI and RRETE, RCETE and RETE, RETE and INF, RRETE and RCETE, SEDU and RCETE, INF and PRI.This attunes to the findings of Omojimite…”
supporting
confidence: 87%
See 1 more Smart Citation
“…However RETE and RCETE are significant at 10% level of significance while PRI is significant at 5% level of significance. This outcome is in line with the results of Idrees and Saddiqi (2013) and Mallick, Das and Pradhan[1] but against the findings of Jelilov, Alenshinloye and Onder[7].The adjustment term (ECM) 1.06 implies that reversion to long run equilibrium is at an adjustment speed of about 106 percent. Finally, the granger causality test reveals that a unidirectional causality exist between SEDU and RETE, PRI and RETE, PRI and RRETE, RCETE and RETE, RETE and INF, RRETE and RCETE, SEDU and RCETE, INF and PRI.This attunes to the findings of Omojimite…”
supporting
confidence: 87%
“…They found that recurrent educational expenditure had direct and significant effect on real GDP in both short run and long run while capital expenditure had direct and insignificant impact on RGDP. Jelilov, Aleshinloye, and Önder [7] investigated the effects of components of education expenditure on economic growth of Nigeria with time series data ranging from 1970 to 2006. Employing ordinary test squares (OLS) technique, the result showed that capital expenditure on education, recurrent expenditure on education, and secondary school enrolment have direct and significant impact on economic growth while primary school enrolment had inverse and insignificant influence on RGDP.…”
Section: Theoretical Proposition and Literature Reviewmentioning
confidence: 99%
“…The neoclassical theories as well as the Tobin's q theory of invest assert that interest rates affect economic growth negatively. For Nigeria, many studies confirm that interest rates are negatively related to economic growth, e.g., Udoka and Roland (2012), Agwu (2014), Orji et al (2015); and Jelilov (2016) and Maiga (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Olu (2012: 483) is of the view that "teachers who shoulder the responsibility of training the young ones need to be developed to be able to perform their role, up-grade and update their competency within the school system". This is particularly important for tertiary education because according to the World Bank, "Education in general and higher education in particular, are fundamental to the construction of a knowledge economy and society in all nations (Jelilov, 2016(Jelilov, : 1863.…”
Section: Introductionmentioning
confidence: 99%